Comparative Glycomics of Immunoglobulin A and G From Saliva and Plasma Reveals Biomarker Potential - Plomp, Rosina; de Haan, Noortje; Bondt, Albert; Murli, Jayshri; Dotz, Viktoria; Wuhrer, Manfred (Frontiers in Immunology, 2018)
The N-glycosylation of immunoglobulin (Ig) G, the major antibody in the circulation of human adults, is well known for its influences on antibody effector functions and its alterations with various diseases. In contrast, knowledge on the role of glycans attached to IgA, which is a key immune defense agent in secretions, is very scarce. In this study we aimed to characterize the glycosylation of salivary (secretory) IgA, including the IgA joining chain (JC) and secretory component (SC) and to compare IgA and IgG glycosylation between human plasma and saliva samples to gain a first insight into oral cavity-specific antibody glycosylation. Plasma and whole saliva were collected from 19 healthy volunteers within a two-hour time window. IgG and IgA were affinity-purified from the two biofluids, followed by tryptic digestion and nanoLC-ESI-QTOF-MS(/MS) analysis. Saliva-derived IgG exhibited a slightly lower galactosylation and sialylation as compared to plasma-derived IgG. Glycosylation of IgA1, IgA2 and the JC showed substantial differences between the biofluids, with salivary proteins exhibiting a higher bisection, and lower galactosylation and sialylation as compared to plasma-derived IgA and JC. Additionally, all seven N-glycosylation sites, characterized on the SC of secretory IgA in saliva, carried highly fucosylated and fully galactosylated diantennary N-glycans. This study lays the basis for future research into the functional role of salivary Ig glycosylation as well as its biomarker potential.